ANALISIS RETURN ON EQUITY (ROE) PADA PT. BANK TABUNGAN NEGARA, TBK - FIQHI PRAYUDA PUTRA; PUJI MUNIARTY; WULANDARI WULANDARI (Universitas Mahasaraswati K. Mataram, 2024)
The objective of this research is to examine the Roe of PT Bank Tabungan Negara, Tbk. This study made use of quantitative descriptive research. Income statements, balance sheets, reports on net profit and equity, and other financial documents covering the years 2013–2022, were culled for this research using a purposeful selection methodology. Statistical analysis with SPSS version 27 and a one-sample t-test are the approaches used for analysis. Return on equity (Roe) for PT Bank Tabungan Negara, Tbk seems to be much lower than 12% for the industry, according to the data that is supplied. If the organization is having trouble meeting its profitability goals, then it has to pay more attention to its financial performance